Acoustic Streaming Caused by Some Types of Aperiodic Sound. Buildup of Acoustic Streaming - PERELOMOVA, Anna; WOJDA, Paweł (Archives of Acoustics, 2009)
The analysis of streaming caused by aperiodic sound of different types (switched on at transducer sound or sound determined by initial conditions) is undertaken. The analysis bases on analytical governing equation for streaming Eulerian velocity, which is a result of decomposition of the hydrodynamic equations into acoustic and non-acoustic parts. Its driving force (of acoustic nature) represents a sum of two terms; one is the classic one, which, being averaged over the sound period, coincides with the well-known expression. The second one depends on the periodicity of the sound; at the axis of beam propagation it becomes exactly zero after averaging for the strictly periodic sound but differs from zero for other acoustic waves. Both terms are nonlinear and proportional to the standard attenuation due to shear, bulk viscosities and thermal conductivity. Numerical analysis reveals a qualitative agreement with experimental data. Some theoretical conclusions concerning features of streaming caused by sound determined by initial conditions, are made.